2014
DOI: 10.1038/ncomms6103
|View full text |Cite
|
Sign up to set email alerts
|

A20 controls intestinal homeostasis through cell-specific activities

Abstract: The transcription factor NF-kB is indispensable for intestinal immune homeostasis, but contributes to chronic inflammation and inflammatory bowel disease (IBD). A20, an inhibitor of both NF-kB and apoptotic signalling, was identified as a susceptibility gene for multiple inflammatory diseases, including IBD. Despite absence of spontaneous intestinal inflammation in intestinal epithelial cell (IEC) specific A20 knockout mice, we found additional myeloid-specific A20 deletion to synergistically drive intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 66 publications
9
98
0
1
Order By: Relevance
“…This was most evident in the distal colon where the inner mucus layer is best developed. This suggests a special mucus niche for this bacterium, something that has also been observed before (Robertson et al, 2005; Vereecke et al, 2014; Belzer et al, 2014). …”
Section: Discussionsupporting
confidence: 80%
“…This was most evident in the distal colon where the inner mucus layer is best developed. This suggests a special mucus niche for this bacterium, something that has also been observed before (Robertson et al, 2005; Vereecke et al, 2014; Belzer et al, 2014). …”
Section: Discussionsupporting
confidence: 80%
“…This interest is due to the revelation that these regulatory proteins significantly attenuate disease pathogenesis in IBD mouse models. For example, prior studies by our group and others have shown that a diverse group of negative regulatory proteins, including NLRP12, NLRX1, TOLLIP, A20, and GIT2, also function to maintain immune system homeostasis in the gut through the attenuation of hyper-responsive inflammation (Mukherjee and Biswas, 2014, Vereecke et al, 2014, Hammer et al, 2011, Boj et al, 2015, Allen et al, 2012, Zaki et al, 2011, Soares et al, 2014, Singh et al, 2015). Many of these negative regulatory proteins have been found dysregulated in IBD and CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, recent study has also shown that mice with the nuclear factor-κB-inducible protein A20 conditional knockout in IECs and myeloid cells (A20 IEC-KO mice) could develop severe colitis because of impaired goblet cells causing reduced mucus. 25 The IECs of A20 IEC-KO mice were found to be sensitive to TNF-induced apoptosis. Thus, A20 possesses a dominant anti-apoptotic effect on IECs, although it could negatively regulate nuclear factor-κB signaling that also plays a role in protecting barrier integrity via inhibiting the apoptosis of IECs.…”
Section: Epithelial Barriermentioning
confidence: 98%